Prehospital Guidelines - Takala Riikka (Springer, 2022)
Prehospital emergency care has an important role in the management of both moderate and severe TBI. The aim of the treatment and care is to prevent and decrease secondary injuries. Securing the airway, maintaining adequate blood pressure, oxygenation and ventilation are the key factors. Additionally, a rapid transport to a hospital with neurosurgical facilities is crucial.
Management of Severe Traumatic Brain Injury